ANALISIS SERVICE QUALITY, PROMOTION, COST STUDY DAN IMAGE DAMPAKNYA PADA MINAT KULIAH DI PERGURUAN TINGGI - Setyowati*, Trias (Universitas Muhammadiyah Jember, 2015)
This study aims to analyze the influence of the quality of service, promotion, education and imaging costs against interest lectures at universities. Problems in this study demonstrated the existence of a phenomenon that occurred since the year 2009/2010 up to 2013/2014 occurred likelihood of fluctuations in the number of applicants or new students who want to study in college education. In this study, will be discussed on a number of factors that may affect interest to continue their education to pursue higher education, among others, the quality of service., Promotion, pricing and imaging. Therefore it is necessary to know how companies in this Institution High peguruan in this case the University of Muhammadiyah Jember as an object of research applying these factors in order to increase the interest of the public, especially students who will continue their education to the level of Higher Education. This study took a sample of 160 new students were scattered at 9 faculties and one college at the University of Muhammadiyah Jember tourism. Analysis of data using multiple linear regression analysis. From the results of the data analysis shows that there is significant influence of four variables: the quality of service by 0243, the promotion of 0172, the cost of education by 0706 and by 0251 the interest of the imaging study at the University of Muhammadiyah Jember.